Penerapan Pembelajaran Berbasis Business Plan Untuk Menanamkan Nilai Produk Kreatif Dan Kewirausahaan Pada Peserta Didik Di SMK - Eka Yuni Purwanti; Amir Mukminin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2021)
The value of entrepreneurship is very important to be developed in schools. This study aims to describe the application of business plan-based learning as a teacher's effort to instill entrepreneurial values ​​in students in SMK. The method used is a qualitative descriptive approach, using an instrumental case study design that focuses on the learning process of the scientific approach and the Business Plan at SMK Gajah Mungkur. Researchers collect data using interviews, observation and documentation which then to determine the validity of the data required inspection techniques. The implementation of the examination technique is based on a number of certain criteria. There are four criteria used to examine it, namely the degree of trust (credibility), transferability (transferability), dependability (dependability) and certainty (confirmability). This is in accordance with stating that the validity of the data in qualitative research includes the credibility test (internal validity), transferability (external validity), dependability (reliability) and confirmability (objectivity). The results of the study indicate that the implementation of learning uses a scientific approach. The teacher assigns students to obtain information through observation of a company and then arranges the idea into a business plan. Emphasis is on the character of daring to take risks, while the attitude of practicing has not been done. Evaluation is carried out on the learning process and results. The teacher has planned, implemented and assessed well and the students enthusiastically get meaningful learning.